Osmotic Characteristics of Erythrocytes After Freezing with Composition-Modified Cryopreservatives - Ramazanov, Viktor; Volovelska, Yelyzaveta; Bondarenko , Valeriy (Problems of Cryobiology and Cryomedicine, 2022)
Here, we have studied the osmotic parameters of erythrocytes frozen in the composition-modified media with glycerol and 1,2-propanediol. A decreased glycerol concentration in a cryopreservative and an increased content of impermeable protective component sorbitol were established to affect the erythrocyte characteristics at different stages of freezing and hypothermic storage. Reduction of 1,2-propanediol and NaCl concentrations when augmenting the sucrose content in cryopreservative agent enabled changing a two-stage mode of erythrocyte freeze-thawing to the single-stage one. The presented here modification of cryoprotective medium allowed to diminish the level of damage to erythrocytes during freeze-thawing-washing out, that might prevent the inflammation development in a body when transfusing these cells. Probl Cryobiol Cryomed 2022; 32(2):092–103